Ag+-Mediated Folding of Long Polyguanine Strands to Double and Quadruple Helixes - Liat Katrivas; Anna Makarovsky; Benjamin Kempinski; Antonio Randazzo; Roberto Improta; Dvir Rotem; Danny Porath; Alexander B. Kotlyar (Nanomaterials, 2024)
Metal-mediated base pairing of DNA has been a topic of extensive research spanning over more than four decades. Precise positioning of a single metal ion by predetermining the DNA sequence, as well as improved conductivity offered by the ions, make these structures interesting candidates in the context of using DNA in nanotechnology. Here, we report the formation and characterization of conjugates of long (kilo bases) homoguanine DNA strands with silver ions. We demonstrate using atomic force microscopy (AFM) and scanning tunneling microscope (STM) that binding of silver ions leads to folding of homoguanine DNA strands in a “hairpin” fashion to yield double-helical, left-handed molecules composed of G-G base pairs each stabilized by a silver ion. Further folding of the DNA–silver conjugate yields linear molecules in which the two halves of the double helix are twisted one against the other in a right-handed fashion. Quantum mechanical calculations on smaller molecular models support the helical twist directions obtained by the high resolution STM analysis. These long guanine-based nanostructures bearing a chain of silver ions have not been synthesized and studied before and are likely to possess conductive properties that will make them attractive candidates for nanoelectronics.